Spelling errors of Arab ESL and EFL secondary school students and their attitudes towards spelling and writing - Alsobhi, Bandar Mohammadsaeed A. (2017)
English spelling has been described as troublesome because it lacks correspondence between its phonemes and graphemes. This makes Arab learners commit serious spelling errors while writing. The current study compares the types and causes of spelling errors made by Arab secondary school students across two contexts, ESL context in Malaysia and EFL context in Saudi Arabia. It also aims at identifying the relationship between the students’ attitude towards spelling and writing as well as examines the relationship between writing ability and spelling accuracy among the Arab students. The study adopted a mixed-method approach in order to acquire a deep understanding of the phenomenon under investigation. The participants of the study included 140 Arab secondary school students and four English language teachers from both contexts. The study involved quantitative and qualitative data collection methods. Whilst the quantitative data of the study was gathered via three instruments, namely, a spelling test, free composition and survey questionnaire, the qualitative data was gathered via face-to-face interviews with English school teachers who were teaching the Arab students in both contexts. As far as data analysis is concerned, the descriptive statistics was carried out to analyse the quantitative data, which were computed and interpreted by means of the SPSS whereas thematic analysis and inductive coding were used to analyse the qualitative data gathered from the interviews. The students’ types of spelling errors were categorised based on Cook’s (1999) classification of errors whereas the likely causes of spelling errors were inferred from the students’ spelling tests and the English teachers’ interviews. The findings of the study indicate that the total number of spelling errors committed by the Arab students in Malaysia was smaller than their counterparts’ in Saudi Arabia. Moreover, errors of substitution represented the highest percentage of errors in both contexts. Accordingly, the likely causes of spelling errors were attributed to the irregularity of English spelling, the students’ limited knowledge of spelling rules and mother tongue interference as well as other non-linguistic factors. The findings also indicate that the Arab students in both contexts have positive attitude towards English spelling and writing. The findings also indicate that there was a significant positive correlation between the attitudes towards spelling and writing among the Arab students in Malaysia, but no significant correlation between the two variables in the Saudi context. The findings also revealed a positive correlation between spelling accuracy and writing ability among the Arab students in Malaysia but no significant correlation among their counterparts in Saudi Arabia. The study concludes that Arab learners in both contexts find English spelling difficult and perplexing. The study recommends that formal spelling instruction should be integrated with writing and reading lessons in the curriculum in order to overcome the students’ spelling deficiency, which in turn, would facilitate the enhancement of ESL/EFL writing.